Aberrant NF-KappaB Expression in Autism Spectrum Condition: A Mechanism for Neuroinflammation - Young, Adam; Campbell, Elaine; Lynch, Sarah; Suckling, John; Powis, Simon (Frontiers in Psychiatry, 2011)
Autism Spectrum Condition (ASC) is recognised as having an inflammatory component. Post mortem brain samples from patients with ASC display neuroglial activation and inflammatory markers in cerebro-spinal fluid, although little is known about the underlying molecular mechanisms. Nuclear factor kappa-light-chain-enhancer of activated B cells (NF-kB) is a protein found in almost all cell types and mediates regulation of immune response by inducing the expression of inflammatory cytokines and chemokines, establishing a feedback mechanism that can produce chronic or excessive inflammation. This article describes immunodetection and immunofluorescence measurements and of NF-kB in human post-mortem samples of orbitofrontal cortex tissue donated to two independent centres: London Brain Bank, Kings College London, UK (ASC: N=3, controls: N=4) and Autism Tissue Program, Harvard Brain Bank, USA (ASC: N=6, controls: N=5). The hypothesis was that concentrations of NF-kB would be elevated, especially in activated microglia in ASC, and pH would be concomitantly reduced (i.e. acidification). Neurons, astrocytes and mircroglia all demonstrated increased extranuclear and nuclear translocated NF-kB p65 expression in samples of brain tissue from ASC donors relative to samples from matched controls. These between-groups differences were increased in astrocytes and microglia relative to neurons, but particularly pronounced for highly mature microglia. Measurement of pH in homogenised samples demonstrated a 0.98 unit difference in means and a strong (F = 98.3; p = 0.00018) linear relationship to the expression of nuclear translocated NF-kB in mature microglia. Acridine orange staining localised pH reductions to lysosomal compartments. In summary, NF-κB is aberrantly expressed in orbitofrontal cortex in patients with ASC as part of a putative molecular cascade leading to inflammation that is potentially responsible for the associated behavioural and clinical symptoms.